IMPLEMENTASI KEBIJAKAN KEMENKES NO.HK.01.07/MENKES/413/2020 TENTANG PEDOMAN PENCEGAHAN DAN PENGENDALIAN COVID-19 OLEH DINAS KESEHATAN KABUPATEN SUMEDANG - dadang Suhendi; Agus Taryadi; Dendi Mulyadi Setiawan; Opi Nurmala; Selly Hartati; Wika Kosmira (LPPM UNSAP & FISIP UNSAP, 2021)
This research discusses the Implementation of Ministry of Health Policy NO.HK.01.07/MENKES/413/2020 concerning guidelines for the prevention and control of covid-19 by the Sumedang District Health Office. This study aims to determine how the Sumedang District Health Office implements the policy, which in its implementation can find out the obstacles faced by the Sumedang District Health Office, as well as efforts to overcome the obstacles faced by the Sumedang District Health Office. This study used a qualitative approach, determining research informants, namely purposive sampling technique, with the Head of the Program and Disease Prevention and Control (P2P) Division and the case study method. The data collection techniques used are literature study and field study consisting of observation, in-depth interviews, and documentation study. The results of this study indicate that the implementation of the Ministry of Health's Policy No.HK.01.07 / MENKES / 413/2020 regarding guidelines for the prevention and control of covid-19 by the Sumedang district health office has been running in accordance with the decision of the minister of health in the prevention and control of covid-19 in Sumedang district. One of the programs made by the Minister of Health of the Republic of Indonesia, in a decree of the Minister of Health NO.HK.01 / 07 / MENKES / 413/2020 concerning Guidelines for the Prevention and Control of Covid-19. Based on the results of this study, the implementation of the Ministry of Health's Policy NO.HK.01.07 / MENKES / 413/2020 regarding the guidelines for the prevention and control of covid-19 by the Sumedang District Health Office has been running according to the decision of the minister of health in the prevention and control of covid-19 in Sumedang district, although socialization is quite good, there is still low public participation in the use of masks.